GC/MS analysis, free radical scavenging, anticancer and beta-glucuronidase inhibitory activities of Trillium govanianum rhizome (Bangladesh Journal of Pharmacology, 2015)
The current study aims to investigate the phytochemical constituents, antioxidant, β-glucuronidase inhibitory and anticancer activities of Trillium govanianum rhizome. Phytochemical screening revealed the presence of steroidal glycosides, saponins, sterols, flavonoids and carbohydrates. GC/MS analyses of n-hexane fraction identified 12 compounds, including 70% unsaturated and 30% saturated fatty acids. Higher free radical scavenging capacity was observed in n-hexane and chloroform fraction compared with the other fractions. Based on IC50 (μg/mL) values, antiproliferative activity on HeLa cells was observed for  chloroform (0.8 ± 0.2), ethyl acetate (1.4 ± 0.1) and butanol (1.6 ± 0.3) fractions by comparison to anticancer drug doxorubicin (0.3 ± 0.0). Similarly, all fractions exhibited cytotoxicity on PC-3 cells. Moreover, the methanol extract (IC50: 140.8 ± 3.8) and butanol fraction (196.2 ± 1.9) exhibited a moderate level of β-glucuronidase inhibitory activity. These findings may validate the folkloric uses of T. govanianum rhizome in cancer management, and can be a promising candidate as an anticancer agent.